Portrait drawings therapy: windows of hope for children with autism spectrum disorder - Yap, Bee Cheng; Mohd Salleh, Amla; Jusoff, Kamaruzaman (IDOSI Publications, 2011)
The paper reports a case study on the ability of a group of children with autistic spectrum disorders (ASD) in recognising face using portrait drawing technique. Sample comprised of four ASDs children and four non-ASDS children and eight teachers. Eight individual drawing sessions were conducted with the children sample. Data were collected using observations, interviews and Portrait Drawing Assessment (PDA) Instrument. Results showed that the two groups of children had different profile. The analysis was also able to identify the drawing developmental stage of each participant. The results imply that drawing technique has a potential to draw autistics children attention and teaching them to recognise faces. This paper concludes that portrait drawing session has a great potential to be an intervention for ASDs children developing communication. As the present study was the first for children with ASD in Malaysia therefore more evidences are required to confirm the finding.